Inclusion‐body myositis and primary Sjögren syndrome: mechanisms for shared etiologies. Issue 5 (15th February 2020) - Limaye, Vidya S.; Cash, Kathy; Smith, Caroline; Koszyca, Barbara; Patel, Sandy; Greenberg, Steven A.; Hissaria, Pravin
Abstract: Herein we report a case of sporadic inclusion‐body myositis (sIBM) occurring at an unusually young age in a patient with primary Sjögren syndrome, and use the case to explore possible shared mechanisms for disease susceptibility. Possible factors may include the association of both conditions with the 8.1 ancestral haplotype; the presence of anti‐cN1A antibodies, which, although considered specific for sIBM, are also seen in pSS; and the shared association with T‐cell large granular lymphocyte leukemia (T‐LGLL). Further evaluation of this patient did in fact reveal underlying T‐LGLL and mechanisms by which T cells in sIBM may escape immune regulation and contribute to disease phenotype are explored. Despite myofiber infiltration with CD8‐positive T cells in sIBM, and, although sIBM is traditionally considered treatment‐refractory, we report a significant response to the anti‐CD20 monoclonal antibody, rituximab, and discuss possible mechanisms by which this response may be mediated.